2002
DOI: 10.1016/s0092-8674(02)00625-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis

Abstract: Defects in apoptosis underpin both tumorigenesis and drug resistance, and because of these defects chemotherapy often fails. Understanding the molecular events that contribute to drug-induced apoptosis, and how tumors evade apoptotic death, provides a paradigm to explain the relationship between cancer genetics and treatment sensitivity and should enable a more rational approach to anticancer drug design and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
613
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,986 publications
(641 citation statements)
references
References 82 publications
11
613
0
1
Order By: Relevance
“…Cancer cells die as a consequence of apoptosis owing to prolonged arrest in either G1/S or G2/M phases of cell cycle or owing to their inability to replicate (Johnstone et al, 2002). We found that diminished viability of cells upon Mid-and 13L-shRNA expression (Figure 5a, c-g) was not due to defective cell proliferation (Figure 5b) or perturbed cell cycle progression (not shown), but was a direct consequence of spontaneous apoptosis.…”
Section: Discussionmentioning
confidence: 74%
“…Cancer cells die as a consequence of apoptosis owing to prolonged arrest in either G1/S or G2/M phases of cell cycle or owing to their inability to replicate (Johnstone et al, 2002). We found that diminished viability of cells upon Mid-and 13L-shRNA expression (Figure 5a, c-g) was not due to defective cell proliferation (Figure 5b) or perturbed cell cycle progression (not shown), but was a direct consequence of spontaneous apoptosis.…”
Section: Discussionmentioning
confidence: 74%
“…As impaired apoptosis plays a central role in oncogenesis, the search is accelerating for novel agents that engage the cell death machinery (Nicholson, 2000;Johnstone et al, 2002). Impaired apoptosis is also a significant impediment to cytotoxic therapy.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Disruption of apoptosis clearly contributes to the pathogenesis of cancer, and is a contributing factor in chemotherapeutic resistance observed in many human tumor cells (Thompson, 1995). Indeed, suppression of apoptosis is a consistent characteristic of tumors and malignantly transformed cells (Johnstone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%